PENGARUH PELAYANAN AKADEMIK TERHADAP TINGKAT KEPUASAN MAHASISWA UNIVERSITAS BANTEN JAYA (UNBAJA) - Khristina Sri Prihatin; Yohana Selvia Dewi (FKIP, Universitas Banten Jaya, 2019)
This research was conducted at University Banten Jaya (UNBAJA). The purpose of this research were: 1) to know how the quality of academic service. 2) to know how student satisfaction. 3) to know how the influence of academic service to the level of student satisfaction. In this research data collection technique was spreading questionnaires for 322 respondents(19,5%) of 1.649 populations. The method used in this research was descriptive. The Data analysis included, validity test, reliability test, classical assumption test (residual normality, heteroscedasticity, linearity), correlation analysis, simple linear regression analysis, significance test (f test, t test,coefficient of determination). The results were data analysis has been done obtained results where the academic services included into the category of